Attempts to Determine the Velocity Variations in Ocean Geostrothrophic Currents Based on GRACE Solutions - Zofia Rzepecka; Monika Birylo (Remote Sensing, 2024)
The paper shows the idea of using GRACE solutions to determine the velocity of the Atlantic geostrophic currents at a depth of 2000 m, where the assumptions of geostrophic motion are met. The relationship between the water velocity variations and the OBP, determined based on the L2 GRACE solutions, is shown. The velocities obtained were compared with the results of a direct ocean current measurement program, the RAPID AMOC, carried out in the Atlantic area. The upper North Atlantic Deep Water layer transport was used for comparisons performed. An analysis of the obtained results, their summary, and discussion are shown. The research covers the period from November 2004 to March 2022. As a result of flow calculations through the parallel, a satisfactory agreement was obtained between the GRACE and RAPID AMOC fitted functions. The correlation between the GRACE and RAPID AMOC time series observations exceeded the significance level.